Weton: Reflections on Employee Interests to Become a Whistleblower - Purwanti, Lilik; Effendi, Soelchan Arief (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 1 (2023)DO - 10.24843/JIAB.2023.v18.i01.p01, 2023)
This study aims to reveal the employee's interest in reporting fraudulent acts in the Universitas Brawijaya Academic Business Entity and analyzes the employee's interest based on the  weton . Informants include the director, deputy director, financial manager, treasurer, and administrative staff. This qualitative research was conducted through unstructured interviews as well as documentation methods to obtain information about  weton  from informants. This study found that some employees were interested and some were not. Whistleblowers with  weton  Rebo Pon ,  Akad Pahing ,  Sênin lêgi  and  Rêbo lêgi  consider reporting fraud an obligation and a moral responsibility because it harms the organization. On the other hand, the whistleblowers with  weton  Kêmis pon  and  Sêtu kliwon  feel uncomfortable, sorry, and afraid to report. The work environment and family form a character that encourages a person's interest in becoming a whistleblower. Keywords:  weton, fraud, employee interest, whistleblower